Lead nephropathy due to Sindoor in India. (July 2013) - Kute, Vivek B.; shrimali, Jigar D.; Balwani, Manish R.; Godhani, Umesh R.; Vanikar, Aruna V.; Shah, Pankaj R.; Gumber, Manoj R.; Patel, Himanshu V.; Trivedi, Hargovind L.
Abstract We report a case of lead nephropathy due to Sindoor treated successfully with steroid, hemodialysis and chelating agent. Diagnosis of lead nephropathy was confirmed by identification of potential sources of lead exposure (Sindoor, 5–10 gm per year for 11 years) indicated by high blood lead level, 95 µg/dL and presence of extrarenal features of lead poisoning (hypertension, anemia, lead line, hyperuricemia). A search for the underlying systemic causes of renal failure yielded no results. A kidney biopsy showed acute or chronic tubule-interstitial nephritis with mesangioproliferative glomerulonephritis with no immune deposit on immunofluorescence consistent with lead nephropathy. He was discharged in good health after psychiatric consultation and continued with oral D-Penicillamine with normal renal function tests and urine output. This case identifies Sindoor as a potential lead exposure among Indians and clinicians should be aware of this risk factor and enquire about it when searching a source of lead exposure in high-risk population.